Crack assessment criteria for ship hull structure based on ship operational life. Issue 1 (1st January 2017) - Nair, Ajit; Sivaprasad, K.; Nandakumar, C.G.
Abstract: Steel ship structures are prone to developing cracks as a result of their all welded construction, material imperfections, loading conditions, fatigue and corrosion. Much of the research in this field has been focussed on crack growth or propagation from a fatigue perspective. However cracks can develop as early as during the construction stage itself and not all of them would be detected and rectified. Normally these cracks may not pose a direct threat to the ship structural integrity but when subjected to a sudden impact force typically associated with collision, allision and grounding accidents, these existing cracks could propagate at a faster rate and lead to structural failure and compromise the tank leak integrity. This paper presents criteria for assessment of cracks based on inducement factors which influence crack initiation in the hull structure even during the early stages of operation. Detectable cracks identified during inspection are analysed to determine the inducement factor and the underlying causes for such crack initiation corresponding to the ship operational life. Subsequent repair work performed will not only resolve the identified inducement factor responsible but also ensure that these cracks will not resurface and pose threat to the structural integrity of the ship, even under sudden impact. A relationship is established between these inducement factors and the ship operational life to simplify the inspection and crack assessment process. The circular data visualization technique is adopted to represent this relationship and a procedure is developed to demonstrate the use of the proposed crack assessment criteria.